Application of Plant Insecticides Basil Leaves (Ocinum basilicum) for Plutella xylostella L. Pest Control on Cabbage Plants - Manikome, Nonice (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
The level of damage caused by P. xylostella reached 75%. Until now, the control still relies on the use of chemical insecticides. Efforts to minimize control with chemicals need to be done because chemical control has a negative impact on health and the environment, one of the environmentally friendly controls that can be applied is the use of plant-based insecticides which of course contain active compounds that can suppress and even kill pests. One type of plant that can be used as a vegetable insecticide is basil (Ocimum basilicum). Researchers conducted research using basil extract as a vegetable insecticide to control Plutella xylostella pests. The method used is the dyeing method (residue on the leaves of the feed). Using a completely randomized design (CRD) with 5 treatments: extract concentration 15%, 25%, 35%, 45% and control, 5 replications. The results showed that the highest mortality was found at a concentration of 45%, namely 80.75%, the higher the killing power because the increase in concentration was directly proportional to the increase in toxic substances, the number of toxic compounds contained in the extract made the mortality high. Based on the results of the study, it can be concluded that basil extract is effective in controlling P. xylostella pests.